Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ejp.651
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism‐based pain sensitivity index to characterize knee osteoarthritis patients with different disease stages and pain levels

Abstract: Radiological scores, contrary to clinical pain intensity/duration, were poorly associated with QST parameters. The pain sensitivity index could classify OA patients with different degrees of OA and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 47 publications
11
124
0
Order By: Relevance
“…Recently, a single pain sensitivity index based on QST z-scores was proposed [2] to characterize the degree of hypersensitivity in this population. However, the varied pain sensitivity profiles observed in this patient cohort support the conclusion by Neziri et al [40] that multimodal pain assessment is necessary for optimal patient characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a single pain sensitivity index based on QST z-scores was proposed [2] to characterize the degree of hypersensitivity in this population. However, the varied pain sensitivity profiles observed in this patient cohort support the conclusion by Neziri et al [40] that multimodal pain assessment is necessary for optimal patient characterization.…”
Section: Discussionmentioning
confidence: 99%
“…47,55,67,77,78) and in some cases, a positive correlation between these traits and chronic pain intensity. 2,16,53 It is thus possible that similar mechanisms are responsible for pain chronification regardless of the origin of the nervous system pathology. The results of this study contribute further by showing that the severity and the extent of CNP distribution may be attributed to different mechanisms; ie, hyperexcitability and loss of inhibitory control, respectively.…”
Section: The Relationship Between Spinothalamic Tract Lesion Centralmentioning
confidence: 96%
“…Recent QST studies in individuals with OA have revealed distinct subgroups consistent with significant central nervous system (CNS) alterations to pain processing and even to predict treatment outcomes [2,3,22,28,30,33]. Whereas most previous investigators have examined QST measures as individual variables, a more sophisticated approach would consider patterns of responses across multiple QST measures.…”
Section: Introductionmentioning
confidence: 99%
“…Although QST phenotypic heterogeneity has been reported in healthy individuals [13,16,25], less is known in knee OA. Recent investigations have used pressure pain thresholds, temporal summation of pressure pain and conditioned pain modulation as a mechanism-based pain sensitivity index to characterize knee OA with different disease stages and pain levels [2] and their associations with post-operative outcomes [46]. Accounting for inter-individual variability in experimental pain may lead to improved translation of results from the laboratory to the clinic.…”
Section: Introductionmentioning
confidence: 99%